INDUCTIVE AND DEDUCTIVE APPROACHES IN FOREIGN LANGUAGE TEACHING - A P Puzanov (Peoples' Friendship University of Russia (RUDN University), 2016)
The article is devoted to the key issue of foreign language teaching - the concept of method - deductive or inductive. The opposition is surveyed and analysed on the basis of foreign research in this field including a spectrum of basic categories and subcategories of the deductive-inductive continuum of explicit and implicit knowledge with all the contradictions, complexity and multi-factor nature of the experimental results. Besides, methodological, philosophic and pedagogical foundations of induction and deduction are considered in the light of achievements of cognive psychology (L.S. Vygotsky, J. Piaget, J. Bruner), constructivism (E. von Glasersfeld), synergetics (I. Prigozhin, L. Bertalanffy, H. Haken), critical pedagogy (H. Giroux, P. McLaren), "episodical learning" (S.I. Gessen), existential philosophy of education (N.A. Berdyaev), problem-based learning (J. Dewey). The range of questions dealt with are as follows: effectiveness of foreign language teaching as a criterion of learning success; ends and means in the process of education; ethical dependence of foreign language learning, in particular pedagogical coercion; inductive strategies in language creative work, linguistic self-organization, development of critical thinking (the principle of discovery, problem-based tasks). Methodological analysis of the problem state and ways of its solution showed divergence of opinion that indicates the necessity of multiple evaluation and complementarity of both inductive and deductive approaches under different conditions and for different purposes. At the same time philosophic and pedagogical view revealed the significance of ethical and motivation factors such as inherent value of learning process, the issue of ends and means in the broad educational context.